Improving Students’ Writing Skill through Outdoor Learning at SMA Negeri 1 Maiwa Kabupaten Enrekang - Hasan, Hasan (Majesty Journal, 2019)
This study aimed to determine whether the use of outdoor learning strategy could improve students’ writing skill at SMA Negeri 1 Maiwa, Enrekang Regency. The study employed a quasi-experimental design involving two groups, namely an experimental group and a control group, with a total sample of 46 tenth-grade students selected through random sampling. Data were collected through pre-test and post-test descriptive writing tasks and were analyzed using mean scores and t-test. The findings revealed that both groups showed improvement after instruction, but the experimental group achieved a higher gain. The mean score of the experimental group increased from 64.6 in the pre-test to 78.7 in the post-test, while the control group improved from 60.8 to 69.9. The t-test result for the post-test was 4.037, which was higher than the t-table value of 2.021, indicating a statistically significant difference between the two groups. Improvement was also evident across the main components of writing, including content, organization, vocabulary, language use, and mechanics. These findings indicate that outdoor learning strategy was effective in improving students’ descriptive writing skill. The strategy helped students generate ideas more easily, develop richer content, and produce better organized writing through direct engagement with their surroundings.